Oil in the Flint Hills - Rex Buchanan (Symphony in the Flint Hills, 2014)
On a December day in 1915, on a rise just north of El Dorado, drillers gathered around a well. They were using a cable tool rig, one that lifts and drops a sharpened iron tool into the ground, pounding a hole into the earth, really, rather than drilling. Back in September and October, they’d seen shows of oil on their way down, at 550 feet and 650 feet. But on this day, at about 2,500 feet, they found more. Much more.
Keywords: oil; rig; drilling; history; Stapleton; Butler county; El Dorado; Cambrian Period; Bartlesville; sand; working; rubberneck; barrels; Greenwood County; Teterville; Cassoday; Kansas Oil Museum; boomtown; gas